Food Standards, Certification, and Poverty among Coffee Farmers in Uganda - Brian Chiputwa; Matin Qaim; David J. Spielman (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2013)
Private standards are gaining in importance in global markets for high-value foods. We analyze and compare impacts of three sustainability oriented standards – Fairtrade, Organic, and UTZ – on the livelihoods of smallholder coffee farmers in Uganda. Using survey data and propensity score matching with multiple treatments, we find that Fairtrade certification increases household living standards by 30% and significantly reduces the prevalence and depth of poverty. For the other two certification schemes, no significant impacts are found. Institutional factors that may explain differential impacts are discussed. Overly general statements about the effects of standards on smallholder livelihoods may be misleading.
Keywords: I32; L15; O12; Q13; Q17; 330; coffee; smallholder farmers; Organic; Fairtrade; impact; Uganda; Africa